Investigating the Practicality of True Federalism in Nigeria - Emmanuel Lucas Nwachukwu (Journal of Social Science, 2023)
The growing frustration among different disenchanted regions of Nigeria raises the question; if Nigeria’s current federal structure is delivering the full benefits of citizenship to every region? This study investigates the practicability of Nigeria’s federalism, taking stock of different challenges confronting the nation-state which are mainly economic and political. The study revealed that the current system of federalism fails to meet the standards of true federalism. This is based on the idea that the autonomy advocated for states and regions is not respected in law or practice. The study therefore recommends restructuring and autonomy, which are meant to give every state and region a sense of belonging, improve unity, create healthy competition and help citizens achieve their aspirations. This will safeguard against a heavy-handed and unfair central government, which will allow states to maintain a degree of autonomy and make decisions that they believe best serve local interests. The study concludes that Nigeria must focus on restructuring and autonomy to drive a decentralized governing structure, which creates balance, preserve the country's national unity and cohesion.